Kebudayaan Kemiskinan pada Tukang Bawak di Makam Jarak Surabaya - Asti Wulandari; Sugeng Harianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study is motivated by the phenomenon of poverty, which is not merely economic but also cultural, particularly among informal workers such as tukang bawak (grave caretakers) in the Makam Jarak Cemetery area, Surabaya. Tukang bawak are individuals who earn a living by maintaining graves as a means of adapting to economic hardship. In practice, this occupation often involves children, giving rise to the intergenerational transmission of the values associated with the culture of poverty. This study aims to analyze the socio-economic conditions of tukang bawak, identify the cultural values that characterize the culture of poverty, and examine the process through which these values are transmitted to children. The research employs a qualitative approach with a verstehen paradigm to understand the meaning of social actions from the participants' perspectives. Data were collected through in-depth interviews, observation, and documentation using a purposive sampling technique. The findings reveal that the socio-economic conditions of tukang bawak are characterized by low educational attainment, unstable income, and a high number of family dependents. The cultural values associated with the culture of poverty include a short-term orientation, fatalistic attitudes, and dependence on external assistance and social networks. These values are transmitted through children's involvement in their parents' work activities, allowing them to become internalized from an early age and thereby increasing the likelihood of perpetuating intergenerational poverty.